Angle-stable interlocking nailing in a canine critical-sized femoral defect model for bone regeneration studies: In pursuit of the principle of the 3R’s - Saunders, W. B.; Dejardin, L. M.; Soltys-Niemann, E. V.; Kaulfus, C. N.; Eichelberger, B. M.; Dobson, L. K.; Weeks, B. R.; Kerwin, S. C.; Gregory, C. A. (Frontiers in Bioengineering and Biotechnology, 2022)
Introduction: Critical-sized long bone defects represent a major therapeutic challenge and current treatment strategies are not without complication. Tissue engineering holds much promise for these debilitating injuries; however, these strategies often fail to successfully translate from rodent studies to the clinical setting. The dog represents a strong model for translational orthopedic studies, however such studies should be optimized in pursuit of the Principle of the 3R’s of animal research (replace, reduce, refine). The objective of this study was to refine a canine critical-sized femoral defect model using an angle-stable interlocking nail (AS-ILN) and reduce total animal numbers by performing imaging, biomechanics, and histology on the same cohort of dogs. Methods: Six skeletally mature hounds underwent a 4 cm mid-diaphyseal femoral ostectomy followed by stabilization with an AS-ILN. Dogs were assigned to autograft (n=3) or negative control (n=3) treatment groups. At 6, 12, and 18 weeks, healing was quantified by ordinal radiographic scoring and quantified CT. After euthanasia, femurs from the autograft group were mechanically evaluated using an established torsional loading protocol. Femurs were subsequently assessed histologically. Results: Surgery was performed without complication and the AS-ILN provided appropriate fixation for the duration of the study. Dogs assigned to the autograft group achieved radiographic union by 12 weeks, whereas the negative control group experienced non-union. At 18 weeks, median bone and soft tissue callus volume were 9,001 mm3 (range: 4,939 – 10,061) for the autograft group and 3,469 mm3 (range: 3,085 – 3,854) for the negative control group. Median torsional stiffness for the operated, autograft treatment group was 0.19 Nm/° (range: 0.19-1.67) and torque at failure was 12.0 Nm (range: 1.7-14.0). Histologically, callus formation and associated endochondral ossification were identified in the autograft treatment group, whereas fibrovascular tissue occupied the critical-sized defect in negative controls. Conclusion: In a canine critical-sized defect model, the AS-ILN and described outcome measures allowed refinement and reduction consistent with the Principle of the 3R’s of ethical animal research. This model is well-suited for future canine translational bone tissue engineering studies.